Seasonal abundance of Sturnella superciliaris (Bonaparte, 1850) in International Airport of Parnaíba, Piaui, Brazil. - Rocha, Lourdiane; Soares dos Santos, Antonio Gildo; Cardoso, Cleiton Oliveira; Gomes, Deimes do Nascimento; Tavares, Antonio Alves; Guzzi, Anderson (Comunicata Scientiae, 2013)
This survey was conducted in order to evaluate the occurrence and seasonality of White-browed- Blackbird, Sturnella superciliaris in Parnaíba International Airport, in view of the risk of collisions between birds and aircraft. The constancy index of species was 99.5%, with the highest mean number of individuals recorded during the rainy season in the region, in April 2011, with 152 individuals. Although S. superciliaris landed or crossed the runway in large flocks, there were no collisions involving this species, which is probably due to the small air traffic at the airport.